Employee Engagement Ditinjau Dari Motivasi Kerja Pada Karyawan - An Riwi Widyastuti; Nanda Tri Adhi Erlangga (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2021)
This study aims to determine the relationship between work motivation and employee engagement. The reasech method used is a quantitative, the collection of data using the employee engagement scale and work motivation scale. The sample used amounted to 61 people. The sampling technique used incidental random sampling technique. Analysis of the data used Spearman correlation. The results of this study indicate that there is a very significant relationship between work motivation and employee engagement on employees in the Institution â€œXâ€. The value F = 126,763; R = 0.826; R2 = 0.682 (p <1%),The hypothesis proposed by the researcher is accepted. The magnitude of the effect of work motivation on employee engagement in this study is shown from the coefficient of determination R2 = 68.2%.